Application of Fe(II)/K2MnO4 as a pre-treatment for controlling UF membrane fouling in drinking water treatment - Yu,W; Graham,NJD (Journal of Membrane Science, 2015)
This paper describes some results of mini-pilot-scale tests concerning the performance of potassium manganate (K2MnO4) as a pre-treatment chemical prior to ultrafiltration. Manganate is an intermediate in the commercial preparation of permanganate and in aqueous reactions MnO42- can act as both an oxidant and a coagulant/adsorbent arising from the formation of insoluble MnO2. In addition, the combination of ferrous sulfate and manganate (Fe/Mn), offers a potentially cheaper and effective combination of pre-oxidant and coagulant compared to the chemicals used currently in water treatment (e.g. ozone, chlorine, ferric sulfate). In comparative tests with conventional ferric sulfate and using simulated raw water, the results showed that Fe/Mn pre-treatment substantially reduced membrane fouling in terms of the rate of trans-membrane pressure development (arising from both external and internal fouling). Fe/Mn pre-treatment was effective in reducing bacterial activity, changing the characteristics of organic matter and decreasing the production of extracellular polymeric substances (EPS) by bacteria. The external fouling in this process was determined by the EPS concentration, and the internal fouling mainly determined by the adsorption of lower MW organic matter to the membrane pores. Fe/Mn pre-treatment reduced the amounts of both types of fouling material within the cake layer and membrane pores in comparison to conventional pre-treatment with ferrous sulfate, most likely through the formation of solid-phase Fe(III) and MnO2 and by MnO42- oxidation, thereby leading to a substantial increase in membrane run time.